Home training for older adults with fall prevention: Review article (Research, Society and Development, 2023)
The incidence of falls among the elderly is considered a public health issue, as they can result in injuries, fractures, reduced functional capacity, hospitalizations, psychological damage, such as fear of falling, and can also lead to death. Therefore, this study aims to review interventional studies in the literature that incorporated home physical activities to prevent falls in the elderly population. The methodology covered a qualitative approach based on materials available in the PubMed (National Library of Medicine) database, published between the years 2013 and 2023. The quantity of materials used in the analyses, after applying the inclusion and exclusion criteria, total 11 articles. Considering the positive results in relation to the rates of falls among the elderly during the interventionist processes presented in most studies (6), and the functional improvements of the target audience provided by the other studies (5), it is concluded that physical exercises and activities that improve physical performance, are a good choice for preventing falls in the studied population. It is hoped that this literature review will help future studies to fill the gaps in the scope of interventional physical exercise practices in older adults at risk of falling.